2022
DOI: 10.3325/cmj.2022.63.16
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for venous and arterial thromboses in hospitalized patients with coronavirus disease 2019: data on 4014 patients from a tertiary center registry

Abstract: Aim To evaluate the burden and predictors of thromboembolic complications in a large real-life cohort of hospitalized patients with established coronavirus disease 2019 (COVID-19). Methods We retrospectively reviewed the records of 4014 consecutive adult patients admitted to a tertiary-level institution because of COVID-19 from March 2020 to March 2021 for the presence of venous and arterial thrombotic events. Results Venous-thromboembolic (V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…The median age was 74 years, IQR (64-82). The median Charlson comorbidity index was 4, IQR ( 3 - 6 ). At hospital admission, 3531 (88%) patients had pneumonia, 3265 (81.3%) required oxygen supplementation therapy, and 3359 (83.7%) presented with severe or critical COVID-19 symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…The median age was 74 years, IQR (64-82). The median Charlson comorbidity index was 4, IQR ( 3 - 6 ). At hospital admission, 3531 (88%) patients had pneumonia, 3265 (81.3%) required oxygen supplementation therapy, and 3359 (83.7%) presented with severe or critical COVID-19 symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…Mechanisms of COVID-19 related thrombosis are incompletely understood. Venous and arterial thrombotic events in patients with severe/critical COVID-19 symptoms may develop despite prior exposure to even therapeutic doses of LWMH [ 9 , 13 ]. In-situ thrombotic events in proximal venous-blood circulation, like localized pulmonary artery thrombosis correlating with areas of pulmonary inflammation, are recognized as a feature of disease [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bistrovic et al have suggested these phenomena might be associated with improved prognosis [ 6 ] and might contribute to favorable outcome of patients with cardiovascular comorbidities like atrial fibrillation [ 8 ]. Venous and arterial thrombotic events are a striking feature of severe COVID-19 [ 9 ], however, relationship of remdesivir use with the risk of thrombotic events is unknown and has not been investigated before. Thus, we aimed to compare the occurrence of venous thromboembolism (VTE) and arterial thrombotic (AT) events among patients hospitalized with COVID-19 who were treated with remdesivir with that among case-matched control patients from our large institutional registry.…”
Section: Introductionmentioning
confidence: 99%
“…DVT evaluation is more easily performed and often unexpectedly high event rates are encountered if screening of asymptomatic patients can be utilized [10] . In contrast to VTE that associates with more severe COVID-19 presentation and high functional impairment, AT seem to be associated with milder severity of COVID-19 symptoms and more clear clinical presentation, often in the context of previously established chronic metabolic comorbidities [4] . Thus, it is not surprising that CHA2DS2-VASC score based on comorbidities seems to perform best for prediction of MI and CVI.…”
mentioning
confidence: 80%
“…VTE (deep venous thrombosis (DVT) and pulmonary embolism (PE)) and AT (myocardial infarction (MI), cerebrovascular insult (CVI), peripheral AT (PT) and mesenterial thrombosis (MT)) were considered if documented by objective imaging and laboratory methods. More details on approach, incidence, clinical context and risk factors for VTE and AT in our dataset have been published previously [4] . We considered IMPROVE [5] , modified IMPROVE [6] , IMPROVEDD [7] , Padua [8] and CHA2DS2-VASC [9] risk scores.…”
mentioning
confidence: 99%